Assessment of ultrasound treatment potential to induce ripening in Seeni and Ambul banana varieties (Musa spp.) - U. Chandrajith Samaranayake; B.D. Rohitha Prasantha; K.A.K. Lakmal Chandrasiri (Energy Nexus)
The aim of this study was to investigate the effect of ultrasound as pre-treatments on the ripening rate of the seeni and ambul banana cultivars in Sri Lanka. Ultrasound treatment of 25 kHz frequency was applied to physiologically matured, freshly harvested seeni and ambul banana fruits for different time periods (0, 10, 20 and 30 min) and analyzed for the storage period o f 4 days at 27±1 °C and 80±5 % relative humidity. The changes in fruit firmness (N), Brix value, pH, pee l color, weight reduction (%), carbon dioxide (CO2) production rate (mL Kg-1 h-1) and antioxidant activity were investigated. The pulp pH and fruit firmness of the banana samples significantly decreased (P < 0.05) with the time of ultrasound treatment between 10–30 min while the lowest values were noted at 30 min treated banana samples. The CO2 production rates and Brix values of banana samples significantly increased (P < 0.05) with the storage time compared to the control sample. The highest percentage of weight reductions was recorded in the 30 min ultrasound-treated banana samples compared to the control samples. At 30 min of ultrasound treatment time, the antioxidant activity of the seeni and ambul banan as increased fr om 12.1–57.7 % and 78.5–95.4 % respectively. Storage time and ultrasound treatment had a significant effect (P < 0.05) on color parameters L* and b* (P < 0.05) during banana ripening. Results showed that the early appearance (1–2 days) of yellow color on the peel of 30 min ultrasound treated seeni and ambul banana fingers compared to the control banana fingers. The results of this study suggested that the ultrasound treatment may provide an alternative method to enhance the rate of ripening and maintain the quality of seeni and ambul banana cultivars.